Factors Related To The Incidence Of Dysmenorrhea In Adolescent Girls At Mts Azhariah Lubuklinggau City - Sari, Sandri Fatika; Darmawansyah, Darmawansyah; Anissa, Kintan (Multidisciplinary Journals, 2024)
Based on a pre-survey of 10 female students, 9 experienced dysmenorrhea during menstruation. Then interviews were conducted with 9 female students who experienced dysmenorrhea, the results were 8 people felt that their activities were disrupted because of the dysmenorrhea experienced, so they felt limited to carry out activities and chose to rest for a while. The purpose of this study is to determine the factors related to the incidence of dysmenorrhea in adolescent girls at MTS Azhariah Lubuklinggau City. The type of research used is analytic survey research with a Cross Sectional approach. The population of this study was MTS students in class VIII and 1X at MTS Azhariah Lubuklinggau City, totaling 54 students. Side taking technique in this research is accidental sampling, Data analysis using univariate and bivariate analysis using chi square. The results of the study showed that the age of menarche respondents in the normal category aged 11-12 years as many as 30 people. Based on the results of the questionnaire, it is known that respondents with menarche age 11 years were 18 people, respondents with menarche age 12 years were 12 people and respondents with menarche age 13 years were 20 people and age 14 years were 5 people. The results of the study also found that the age of menarche with abnormal categories of age < 12 years and > 14 years was 48 people with details of menarche age < 12 years 48 people and menarche age 14 years as many as 7 people. The researcher suggested that the MTS should be able to work with the Health Center in the relevant area to hold counselling activities regarding dysmenorrhea continuously for students to improve the reproductive health of female students and study concentration of learning.